A municipalização do ensino fundamental (anos iniciais) no estado de Minas Gerais: Proposta instituída pelo projeto mãos dadas do governador Romeu Zema - 2019/2026 - Santos, Janiely dos (2024)
This master's dissertation is part of the Stricto Sensu Graduate Program in Education at Uberlândia Federal University, framed within the research line "Work, Society, and Education." The research explores the municipalization of primary education (early years) in the state of Minas Gerais, Brazil, focusing on the legislative proposal established by Bill No. 2.657/21, Hands Together. The main objective is to analyze the implementation and impacts of neoliberal educational policies on teaching work in Elementary Level Education in Minas Gerais and the implications for the profession, with attention to the municipalization project Hands Together, proposed by Governor Zema tenure. The methodology employs documentary and bibliographic research, wherein literature review and analysis of legal documents such as Elementary Education Guideline Law Resolution number 9.394/96, the highlighted bill, management plans, and videos of public hearings are conducted. The theoretical framework draws on thinkers like Karl Marx (2017), Harry Braverman (1980), Ricardo Antunes (2009), Antônio Nóvoa (1991), Maurice Tardif (2002), and Dermeval Saviani (1991). The study addresses the dialectical relationship between education and work, as well as the transformations resulting from the productive restructuring process. This study concluded that the results pointed to a worrying precarization of teachers' working conditions, reflecting a perspective that neglects the needs and voice of education professionals. The Hands Together project, in particular, contributes to this trend by promoting municipalization that overburdens municipalities without adequate structural and financial support, thus facilitating the privatization of public education. This process is evidenced by increased labor conflicts and the general deterioration of educational quality, standing out in the context of the neoliberal reforms undertaken by the government of Minas Gerais.